Perancangan Data Warehouse Dalam Mendukung Perusahaan Jasa Pengiriman (PT Tiki Palembang) - Muhammad Adrezo (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Abstract The role of technology is currently needed by an organization. Data warehouse as one of the applications of technology is also widely adopted by various organizations to improve performance. Data warehouse is data that is built to help analyze the situation of an organization or company that has a strategic nature. The development of this data warehouse can produce information. The information generated from the analysis of the data warehouse helps the leadership in making organizational or company development decisions. PT TIKI Palembang as a company engaged in the field of freight forwarding services, in its business processes it is necessary to evaluate and monitor the company's performance. For this reason, it is necessary to build a data warehouse to evaluate performance and maintain the company's competitive advantage. In this study, building a data warehouse using the nine-step methodology in developing a data warehouse in goods delivery services. The implementation of this data warehouse uses the Pentaho application. The built data warehouse can provide information through tables and graphs for management about company performance.